Designing and developing a "Rhythm of Life" as a pedagogy that assists in the cultivation of missional disciple formation - Niemandt, Cornelius Johannes Petrus (Nelus) (University of Pretoria, 2022)
Thesis (PhD)--University of Pretoria, 2021.